2019
DOI: 10.1504/ijep.2019.104523
|View full text |Cite
|
Sign up to set email alerts
|

Applying WRF-CMAQ models for assessment of sulphur and nitrogen deposition in Bulgaria for the years 2016 and 2017

Abstract: Wet, dry and total depositions of sulphur (S) and nitrogen (N) in Bulgaria are simulated on an annual and seasonal basis for the years 2016 and 2017 using WRF-CMAQ (9 km grid resolution). The mean annual values for wet depositions are about 1,300 kg.km -2 , the dry depositions are slightly lower for S and significantly lower for N (180 kg.km -2 ). The highest modelled wet depositions are in the western and south-western parts of the country, the highest dry depositions -in the northern and eastern parts. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The method involves linear correction of model wet depositions by the ratio of the observed to estimated precipitation. In previous studies, [25,29] it was shown that the PBA approach led to improvement of monthly wet depositions in Bulgaria when comparing the model to observed values at single sites. Sensitivity tests on the effect of PBA on monthly wet depositions in Bulgaria suggested a decrease in annual wet depositions by about 25-30%, [31].…”
Section: Brief Overview Of Bgcwfs and Emep-ctmmentioning
confidence: 97%
See 4 more Smart Citations
“…The method involves linear correction of model wet depositions by the ratio of the observed to estimated precipitation. In previous studies, [25,29] it was shown that the PBA approach led to improvement of monthly wet depositions in Bulgaria when comparing the model to observed values at single sites. Sensitivity tests on the effect of PBA on monthly wet depositions in Bulgaria suggested a decrease in annual wet depositions by about 25-30%, [31].…”
Section: Brief Overview Of Bgcwfs and Emep-ctmmentioning
confidence: 97%
“…One of the reasons for this was the difference in the amount of accumulated precipitations for the studied period, with values at Ahtopol lower by more than 20% compared to values in Sofia. The number of days with precipitation in Ahtopol was also less (16) than in Sofia (25), suggesting that the removal of pollutants in Sofia was mainly through the wet deposition. Higher dry depositions of sulfur in Ahtopol in summer months (June to August) could be linked also to influence from the industrial plant "Lukoil Neftochim" Burgas, the largest refinery in the Balkans, located at about 60 km northwards.…”
Section: Comparison To Dry Depositions At Two Sitesmentioning
confidence: 99%
See 3 more Smart Citations